LITERARY IMITATION IN SERVICE OF CULTURAL MEMORY – THE COMPARATIVE ANALYSIS OF “NICHIRIN” BY YOKOMITSU RIICHI AND “SALAMMBÔ” BY GUSTAVE FLAUBERT - Kelner, Hanna (Porównania, 2019)
The article Literary imitation in service of cultural memory – the comparative analysis of “Nichirin” by Yokomitsu Riichi and “Salammbô” by Gustave Flaubert subjects the two novels to comparative analysis, showing how Yokomitsu, inspired by Flaubert’s work, imitates his novel and transposes it into the Japanese culture. It describes the similarities between the plots, the characters and stylistic devices – from the style of description through language to the creation of associative links. The latter similarity is shown via linguistic analysis of text bases. The article analyses how all the elements build a textual monument and how they influence the cultural memory of the readers.